2016
DOI: 10.1097/ncc.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning and Experience of Patients Undergoing Rectal High-Dose-Rate Brachytherapy

Abstract: Clinical teams can tailor their procedural behavior (eg, using certain language, psychosocial interventions) according to patients' needs to increase patients' comfort and ultimately improve their experience of HDR rectal brachytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…It varied from, “sometimes it hurt” (Pt6PostB:4, 11) , to “I felt sore,” (Pt8PostB:5); “She had the pain,” (Translator; Pt3PostB:12) , to “Was very painful” (Pt4Exit:7); “Brachy is very sore,” (Pt7Exit:7 ), and “It was so painful,” (Pt9Exit:20) . In a rectal brachytherapy study it was found that the patients, who were mostly males, who experienced the lithotomy position for the instrumentation aspect similar to this current study for the cervical cancer was very traumatising [ 35 ]. Women linked their experiences to previous familiar experiences, such as the pain of giving birth, or undergoing a pap smear [ 35 ].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…It varied from, “sometimes it hurt” (Pt6PostB:4, 11) , to “I felt sore,” (Pt8PostB:5); “She had the pain,” (Translator; Pt3PostB:12) , to “Was very painful” (Pt4Exit:7); “Brachy is very sore,” (Pt7Exit:7 ), and “It was so painful,” (Pt9Exit:20) . In a rectal brachytherapy study it was found that the patients, who were mostly males, who experienced the lithotomy position for the instrumentation aspect similar to this current study for the cervical cancer was very traumatising [ 35 ]. Women linked their experiences to previous familiar experiences, such as the pain of giving birth, or undergoing a pap smear [ 35 ].…”
Section: Discussionmentioning
confidence: 70%
“…In a rectal brachytherapy study it was found that the patients, who were mostly males, who experienced the lithotomy position for the instrumentation aspect similar to this current study for the cervical cancer was very traumatising [ 35 ]. Women linked their experiences to previous familiar experiences, such as the pain of giving birth, or undergoing a pap smear [ 35 ]. Whereas the males felt embarrassed and exposed and found the lithotomy treatment position disempowering, intrusive and left them feeling vulnerable [ 35 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, patient‐centered information gives many patients a greater health locus of control, which has been linked to better long‐term health‐related quality of life (QOL) . Information, the capacity to participate in decision making, and a degree of control over the treatment decision improves adjustment in many patients …”
Section: Introductionmentioning
confidence: 99%